DEATH AND DESPAIR IN THE POETRY OF TORU DUTT - Suman Sigroha (Soegijapranata Catholic University, 2014)
Compared to the short time that she lived Toru Dutt's literary output as a poet was prodigious. Her yearning for the past and her deep sense of many faceted losses are apparent in her poetry. The evocative acceptance of approaching death in one so young presents a picture of a girl mature beyond her years. A study of her poetry reveals her close affinity with the Romantic poets. Referring to various poems of Toru Dutt, the paper studies the role that religion, and her interpretation of religion/s she was exposed to, has to play in this embracing of the inevitability of fate. This paper analyses the reasons for the presence of the elements of death, despair, nostalgia and a yearning for the past and the role that religion plays in her acceptance of the inevitability of death in the poetry of Toru Dutt. Through a critical examination of various poems, the paper tries to uncover the beautiful interplay of memories of past experiences, stories heard long ago and the moments in the present in Dutt's poetry. It traces the journey of the poet from her exposure to death, to a questioning of death, its nature and the forms it might take, to the final acceptance of death as something as inevitable and precious as love.